Аpplication of modern information resources in teaching students biophysics correspondence courses - Ivanchenko, E. Z.; Denisenko, O. N.; Melnikova, O. Z. (Zaporozhye Medical Journal, 2013)
Presented the experience of application of modern information resources for increase in efficiency of teaching by creation on their basis of lectures computer presentations on biophysics.